Low-fat no-fat Thai : over 190 delicious and authentic recipes from Thailand, Burma, Indonesia, Malaysia and the Philippines - Bamforth, Jane (London : Lorenz Books, 2006)
Includes a comprehensive guide to the authentic ingredients and culinary techniques of Thailand and south-east Asia, and how to adapt them in the modern low-fat kitchen. This work offers recipes for every occasion, including appetizers, soups, salads, poultry and meat, vegetables, fish and seafood as well as desserts
1. Introduction -- 2. The low-fat Thai and South-East Asian kitchen -- 3. Soups -- 4. Appetizers and light bites -- 5. Vegetarian main dishes -- 6. Fish and shellfish -- 7. Chicken and duck -- 8. Meat dishes -- 9. Rice and noodles -- 10. Vegetables and salads -- 11. Desserts -- 12. Glossary -- 13. Map
Includex index
Keywords: Cooking, Asian; Cooking, Thai; Low-fat diet -- Recipes